Fostering empathy through Experience: Assessing the outcomes of the Family Adoption Program (FAP) among indian medical graduates - Priyanka Gupta; Nandini Sharma; Deepanshi Saxena (Clinical Epidemiology and Global Health)
Introduction: The Family Adoption Program (FAP) is integrated into India's Competency-Based Medical Education to enhance medical students' understanding of community health by assigning them to adopt families, thereby fostering empathy and improving patient care. Thus, the study aimed to assess and evaluate its outcomes among medical students and its impact on adopted families. Methods: A cross-sectional study was conducted involving medical students and their adopted families in FAP in Gurugram, Haryana. Data were collected through structured questionnaires focusing on the program's influence on both the students and their adopted families. The university priority health card was issued to all adopted families. Descriptive analysis was done using SPSS v. 28 software. Results: In this study, 123 students and 369 adopted families were included. The majority, (115, 93.5 %) of students reported enhanced communication skills. Most 93.8 % of the adopted families considered FAP as a good initiative. A total of 321 (87 %) families appreciated university priority health cards with the benefits of free services. Conclusion: FAP significantly benefits medical students by enriching their educational experience and fostering empathy. Concurrently, it positively impacts adopted families by improving their health awareness and access to care, highlighting the program's dual advantage in medical education and community health. Since the study was conducted over a brief period without extended follow-up, it was not possible to evaluate the long-term benefits for students and families.